Aspekty procesów upodmiotowienia mieszkańców w społecznościach lokalnych - Machaj, Irena (Wydział Prawa i Administracji UAM, 1991)
The author distinguishes two different perspectives of considerations on social subjectivity: the considerations from the perspective of active individuals, and from the perspective of social structures which may undergo modifications under the influence of actions taken by individuals. The subject-matter of the article are the following issues: the realization by the individual of the role of a member of a local community: the participation in groups appearing within a local community; the formation of the feeling of belonging to a particular social group; and social cooperation within such a group.
Some aspects of the processes of restoring autonomy of members of local communities